Mundane metrolingualism. Issue 2 (3rd April 2019) - Pennycook, Alastair; Otsuji, Emi
ABSTRACT: Drawing on data from a Bangladeshi-run mixed-goods store in Tokyo – a site of diversity in terms of customers, the products and interactions – we argue in this paper that in order to understand translinguistic ordinariness, or what we call mundane metrolingualism, we have to explore both the ideas of ordinariness and of diversity in greater depth. Ordinariness, or the cluster of other terms that have been similarly used (everyday, unremarkable, mundane, from below) has been employed to address four principal concerns: Difference – social, cultural, sexual, economic, racial – rather than commonality is the core experience of human life; diversity is not exotic or something that others have, but key to all experience; diversity has temporal dimensions as part of repeated everyday practice; and difference as everyday practice is part of the non-elite world of struggle for recognition. Focusing on two particular spatiotemporal themes, everydayness and simultaneity, we examine the ways in which different activities, conversations and artefacts may be brought together through mobile technologies. These mundane metrolingual assemblages are both central to the activities of the shop but also part of simultaneous worlds of engagement and activity.